2006
DOI: 10.1038/emm.2006.76
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological comparisons of codon usage patterns among HIV-1 isolates from Asia, Europe, Africa and the Americas

Abstract: To investigate the genomic properties of HIV-1, we collected 3,081 sequences from the HIV Sequence Database. The sequences were categorized according to sampling region, country, year, subtype, gene name, and sequence and were saved in a database constructed for this study. The relative synonymous codon usage (RSCU) values of matrix, capsid, and gp120 and gp41 genes were calculated using correspondence analysis. The synonymous codon usage patterns based on the geographical regions of African countries showed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Up to now, it is unclear how FMDV serotypes might affect codon choice in FMD viruses and we used RSCU [42], ENC [32], COA [43,44] and GC 3S , to measure the synonymous codon usage bias in order to minimize the effects of serotypes on codon bias, which have been successfully used to analyze the variation of codon usage among different viruses species [11,13,14,22,45,46]. The analysis revealed that codon usage bias is low in most cases.…”
Section: Discussionmentioning
confidence: 98%
“…Up to now, it is unclear how FMDV serotypes might affect codon choice in FMD viruses and we used RSCU [42], ENC [32], COA [43,44] and GC 3S , to measure the synonymous codon usage bias in order to minimize the effects of serotypes on codon bias, which have been successfully used to analyze the variation of codon usage among different viruses species [11,13,14,22,45,46]. The analysis revealed that codon usage bias is low in most cases.…”
Section: Discussionmentioning
confidence: 98%
“…Being a rapidly evolving pathogen, codon usage pattern similar to host may help HIV-1 to attain higher gene expression, development of drug resistance, and immune evasion at the same time resulting in mutational robustness and translational selection [8] , [13] . Most evolutionary studies on codon usage of HIV-1 have focused on either the specific codons under selection or compared the codon usage pattern of structural genes in different geographical locations [32] [35] , [51] . Our population level studies of the “Relative neutrality plot” ( Figure 2A ) and “Effective number of codons” ( Figure 2B ) of all genes of HIV-1 indicate that genetic compositional constraints may not be the primary reason for the observed codon usage bias in HIV-1 genes, and translational selection may underlie this feature.…”
Section: Discussionmentioning
confidence: 99%
“…At the population level also, various studies have demonstrated similar selection of functionally important sites in different HIV-1 subtypes, arguing for presence of positive selection [33], [34]. Contrary to these studies, genetic/mutational drift has also been shown to drive evolution of HIV-1 in inter-host transmission, as immune selection changes with change in individual host [17], [35]. Given these opposing results, a clear understanding of the mechanisms leading to host-specific adaptation of the virus, both within a particular individual and at the population level, can provide plausible targets for drug therapy and help to develop effective vaccines.…”
Section: Introductionmentioning
confidence: 99%
“…Codon usage bias has been studied in various organisms ranging from virus to eukaryote, and optimized codon usages in the target viral genes also have been made to improve the efficacy of DNA vaccines development ( Ramakrishna et al, 2004 ; Shackelton et al, 2006 ; van Hemert et al, 2007 ; Wang et al, 2006a , 2006b ). Based on our previous studies, synonymous codon usage itself among RNA viruses such as influenza A viruses and HIV-1s revealed specific bias on the basis of each region, subtype, host or occurring-year group, suggesting that there might be some correlations between the codon usage patterns and viral variations in the codon basis ( Ahn and Son, 2006 , 2007 ; Ahn et al, 2006 ).…”
Section: Discussionmentioning
confidence: 90%
“…They suggested that the main reason for these differences might be due to the differences in the viral replication and repairing mechanisms, such as cellular or viral replicative machinery. In our previous study, synonymous codon usage patterns among RNA viruses such as influenza A viruses and HIV-1s were divided into each region, subtype, host or occurring-year group, with an expectation that there might be some correlations between the nucleotide patterns and the direction of viral variations on the codon basis ( Ahn and Son, 2006 , 2007 ; Ahn et al, 2006 ). Furthermore, van Hemert et al ( 2007 ) reported that the recent evolution of astroviruses was associated with a switch in nucleotide composition and codon usage among non-human mammalian versus human/avian astroviruses.…”
Section: Introductionmentioning
confidence: 99%